Self-Healing Carbon Fiber Composites with Thermoplastic Polymers - Gokcenur Saglam; Ayse Celik Bedeloglu (Journal of Innovative Science and Engineering, 2022)
The utilization areas of composite materials are increasing day by day. However, these materials are difficult and expensive to manufacture. In addition, since they are thermoset structures, their recycling is very limited in case of damage. Self-healing materials are the ones that automatically and independently heal or repair the damage caused by any factors, without external intervention. Self-healing polymeric materials are in the range of smart materials. Research on self-healing polymers and polymer composites using this effect has increased rapidly in recent years due to the advantages such as cost reduction and less labour requirement that the current topic provides. In this review, first of all, brief information about self-healing mechanisms used in composites will be given in the light of the studies in literature, then the use of stitch method in composites and self-healing composites will be mentioned and finally, the test methods of self-healing composites will be addressed.